Germany and the American Revolution, 1770-1800. A sociohistorical investigation of late eighteenth-century political thinking. Transl. by Bernhard A. Uhlendorf. With a forew. by R[obert] R[oswell] Palmer (University of North Carolina Pr., 1977)
Bibl., index.